Transcriptional dynamics and functions of WUSCHEL-related homeobox (WOX) genes from Ginkgo biloba in tissue culture - Wei Xu; Ang Xu; Pingjun Xu; Jiaqi Li; Chao Luo; Xiaoming Yang; Meiling Ming; Yuhua Liu; Guibin Wang; Liangjiao Xue; Fuliang Cao; Gaiping Wang; et al. (BMC Plant Biology)
Abstract Background In vitro regeneration presents significant challenges for the propagation and genetic improvement of most woody plants, particularly gymnosperms. The WUSCHEL-related homeobox (WOX) genes are known to play vital roles as growth regulators in tissue culture regeneration in several plant species. However, the specific functions of WOX genes in the regeneration processes of gymnosperms had not been previously elucidated. This study aims to systematically identify and analyze the WOX gene family in Ginkgo biloba to understand its potential role in tissue culture regeneration. Results Thirteen WOX genes from Ginkgo biloba, designated as GbWUS and GbWOXs, were systematically identified. Phylogenetic analysis revealed the presence of nine genes in the WUSCHEL (WUS) clade, one in the intermediate clade, and three in the ancient clade. Transcriptome analysis indicated tissue-specific expression of seven GbWOXs, with two gymnosperm-specific GbWOXs characterized by extra-long introns exhibiting constitutive expression. Further investigation through Ginkgo tissue culture indicated that GbWOX2 was specifically expressed in embryos and facilitated callus induction, while GbWOX3A showed preferential expression during the early stages of embryo and callus development. Co-expression and Gene Ontology (GO) enrichment analyses suggested interactions and functional roles among GbWOXs. Three genes (GbWOX1, GbWOX2, and GbWOX3A) were then cloned and transformed into poplar and/or tobacco. Overexpression of GbWOX2 resulted in larger and denser callus formation, whereas GbWOX3A effectively enhanced shoot regeneration and noticeably increased the rate of adventitious shoot induction. Conclusions This study provides the first comprehensive analysis of the WOX gene family in Ginkgo biloba and highlights its significant role in tissue culture regeneration. The findings suggest that specific GbWOXs are critical for embryo development and callus regeneration, which provides the foundation for the establishment of effective tissue culture systems in Ginkgo. Moreover, this research contributes valuable insights that could be beneficial for improving propagation techniques and genetic studies in other forest trees, especially within the gymnosperm group.